Determinants of Students' Critical Thinking Skills in Economics Learning: Digital Literacy, Peers, and Learning Discipline - Reni Ananta; Indri Murniawaty (UM Purwokerto Press, 2026)
Critical thinking skills in economics learning are important for evaluating information and making evidence-based decisions, but preliminary observations indicate uneven achievement, particularly in inference. This study examines the partial and simultaneous effects of digital literacy, peer support, and learning discipline on critical thinking skills. A quantitative causal-associative survey was conducted with 137 of 208 Grade XI students selected through proportional random sampling. Data were collected using a four-point Likert-scale questionnaire that met validity and reliability requirements and were then analyzed using descriptive statistics and multiple linear regression. Digital literacy (B = 0.236, p = 0.001), peer support (B = 0.185, p = 0.009), and learning discipline (B = 0.365, p < 0.001) each had a positive and significant effect. The regression model was significant (F = 49.116, p < 0.001) and explained 51.5% of the variation in critical thinking skills, with learning discipline making the strongest standardized contribution. The findings indicate that critical thinking skills are strengthened when students are able to evaluate digital information, test ideas through peer interaction, and regulate learning consistently. Economics learning needs to integrate source verification, structured collaboration, and reflective learning routines.